HUBUNGAN TINGKAT KESEGARAN JASMANI DENGAN HASIL BELAJAR PENDIDIKAN JASMANI SISWA PUTRA KELAS VIII SMP NEGERI 3 INUMAN KUANTAN SINGINGI - Gunawan, Indra Gunawan; Juita, Ardiah Juita; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The problem in this study originated from author observations that  encountered in the field, that found the low results of learning outcomes due to lack of physical freshness of the students. It can be seen during the study, there are many students are yawning during the learning. Then students are much less passionate during learning activities, there are so many students who complain with tiredness, though they just run for one lap only. The purpose of this study was to determine the relationship of physical freshness level with learning outcomes of physical education of a male students of class VII in SMP Negeri 3 Kuantan Singingi. This kind of research is correlational. The population in this study is the male students of class VIII students in SMP Negeri 3 Inuman Kuantan Singingi which it has 32 people by using Total Sampling technique, where the entire population becomes sample, so the sample in this study amounted to 32 people. To obtain research data, it is used Physical Freshness Tests Indonesia (TKJI) and the results of semester report card. The research data that has been obtained were analyzed with a simple product moment correlation. Based on the results of research that has been described in the previous chapter, it can be concluded that there is a relationship of physical freshness level with learning outcomes of physical education of a male students of class VII in SMP Negeri 3 Kuantan Singingi, characterized by rhitung (0.395)> rtabel (0.355). Key words: Physical Freshness, Learning Outcomes